THE ROLE OF VOCABULARY KNOWLEDGE IN LISTENING (Ustozlar uchun, 2024)
ANNOTATION Vocabulary knowledge is essential for effective listening comprehension. It enables listeners to recognize words, understand meanings, and interpret spoken messages accurately. A strong vocabulary aids in processing speech quickly, understanding context, and reducing cognitive load. It is particularly important in academic and professional settings, where complex language and technical terms are often used. Developing vocabulary through exposure to diverse listening materials enhances fluency and comprehension.